Short Story Learning with Project Based Learning to Foster Empathy and Creativity: Belajar Cerpen Melalui Pembelajaran Berbasis Proyek untuk Mengembangkan Empati dan Kreativitas - Aslam, Hafidhan; Venika, Deby; Aji, Ibrahim; Kusmana, Suherli; Nurzaman, Bela (Indonesian Journal of Innovation Studies, 2025)
General background: The cultivation of empathy and creativity is crucial in secondary education, particularly in literary learning. Specific background: However, many students exhibit limited empathetic engagement and creative expression when learning short stories. Knowledge gap: Previous studies on Project Based Learning (PjBL) in literature often overlook its differential effects on empathy versus creativity. Aims: This study investigates the effectiveness of PjBL in enhancing empathy and creative writing skills through short story learning in Grade VIII students of SMP Negeri 1 Plumbon Cirebon. Results: Using a quasi-experimental pretest–posttest control group design, data were collected via short story writing tests, empathy questionnaires, project assessments, and classroom observations, analyzed with paired t-tests, independent t-tests, and simple linear regression. Findings reveal that PjBL implementation followed the prescribed syntax, promoted active participation, and produced short stories rich in empathetic and creative elements. While empathy improved significantly within the experimental group, intergroup comparisons and regression indicated no statistically significant effect on empathy, but a significant positive effect on creativity. Novelty: This research distinguishes the distinct impact of PjBL on two character dimensions in literature learning. Implications: PjBL is a promising pedagogical strategy to foster students’ creative capacity in literary contexts. Highlights: Significant boost in students’ creative writing skills. Empathy improved but not statistically significant between groups. PjBL effectively engages students in literary learning. Keywords: Project Based Learning, Short Story, Empathy, Creativity, Secondary Education